Challenging empowerment: AIDS-affected southern African children and the need for a multi-level relational approach. (January 2014) - Ansell, Nicola
Critics of empowerment have highlighted the concept's mutability, focus on individual transformation, one-dimensionality and challenges of operationalisation. Relating these critiques to children's empowerment raises new challenges. Drawing on scholarship on children's subjecthood and exercise of power, alongside empirical research with children affected by AIDS, I argue that empowerment envisaged as individual self-transformation and increased capacity to act independently offers little basis for progressive change. Rather it is essential to adopt a relational approach that recognises the need to transform power relationships at multiple levels. This analysis has implications for our wider understanding of empowerment in the 21st century.